Critical Analysis of Advertising: Enhancing Identity Construction in EFL Classrooms (2018)
Critical media literacy is a competence that promotes the analysis of messages and strategies used by mass media through the enhancement and implementation of critical skills. This research report describes what a process of critical analysis of advertisements revealed about a group of twenty-one tenth graders’ identity construction at a private institution in Duitama (Boyacá – Colombia). The implementation of eight task- based workshops led them to reflect about the role of advertising in their contexts and its relationship with their identity construction process. As a result, the tasks developed during the workshops guided students in understanding the role advertising plays in their daily life.